Neuromuscular fatigue measures after prolonged concentric - eccentric isokinetic quadriceps activity - Knicker, A. J.; Schmieder, P.; Fricke, H.; Edeler, C.; Rojas, S.; Strüder, H. K. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In experimental protocols fatigue has been studied during isometric contractions or in pre/post fatigue conditions. (Cairns et al. 2005; Knicker et al. 2011). Our study wanted to reveal central and peripheral fatigue during long lasting maximum concentric eccentric contraction conditions for quadriceps muscles in isokinetic mode. Methods: 37 healthy male subjects took part in the study. Isometric (ICC) torque, muscle activation, resting twitch responses were measured with the subjects sitting upright on a dynamometer in three different knee angle positions both before and after 50 fatiguing isokinetic (40 deg./s), kneeflexions (eccentric) (ECC), kneeextensions (concentric)(CCC) at submaximal (75%) effort over a kneeangle ROM of 80deg. Bipolar Surface EMG readings were obtained from selected quadriceps femoris muscles during all contraction conditions. Results: During ICC the fatigue protocol caused a shift of voluntary and stimulated torque-angle relations towards lower kneeangles. Level of activation decreased by app. 36% in the pre / post fatigue comparison with biggest deviations in the most extended kneeposition. During ECC and CCC a steady decline of mean and maximum toque values could be identified in the course of contractions until a stable level of generated torque was achieved after 20 to 30 repetitions for CCC and 15 to 25 repetitions for ECC. Post fatigue values ranged from 32,4% to 63,6% compared to pretest. Decreased EMG median frequencies for all muscles were identified in the pre - post comparison of ICC in all knee angles and during ECC and CCC in phase to the time course of decline of torque values. Central fatigue was estimated via twitch interpolation under ICC, ranged from 13,7% to 31,3% and was evident in the most extended knee position. Discussion: Peripheral and central fatigue effects could be identified as a consequence of the underlying contraction protocol. The exercise protocol caused severe declines of force output which can be attributed to inhibition of MUAPs as the force decrease was accompanied by a pronounced downshift of the EMG median frequency due to a) deteriorated exitationcontraction coupling at cellular level, b) actin-myosin interactions. As the target force output was 75% of maximum effort the muscles compensated the loss of contraction force by recruitment of additional MUs. Central fatigue can develop in all structures above the neuromuscular interface and can also involve motivational aspects.